Assessment Of Pathogens And Water Quality In Residential Swimming Pools In Ampang, Selangor, Malaysia - Zarini Ismail; Shalinawati Ramli; Nurul Azmawati Mohamed @ Abd Aziz; Muslimah Ithnin (UPM Press, 2024)
Indexed by Scopus